Clubfoot in Malawi: local theories of causation. - Bedford, K; Chidothi, P; Sakala, H; Cashman, J; Lavy, C (2011)
This paper examines local theories of the causation of clubfoot expressed by the guardians of children undergoing treatment at clinics run by the Malawi National Clubfoot Programme (MNCP). Core data was collected and analysed using qualitative methodologies of critical medical anthropology. Sixty detailed case studies were completed, each based on an extended open-ended interview with patient guardians. Five main theories of causation were put forward: God; the devil; witchcraft or curses; biological reasons; and inherited condition. Each was elaborated in a variety of ways. There is growing international recognition of the importance of examining the relationship between culture and disability. This study is the first attempt to do so for clubfoot in Malawi. It provides a platform on which to build future qualitative research that can be harnessed by the MNCP and similar initiatives to develop their knowledge base and service provision, both in Malawi and the wider African context.